Tessituras dos territórios de identidade na Bahia: gestão territorial, trajetórias e vivências coletivas de participação - Souza, Silvia Cristina Arantes de (2021)
This thesis deals with the experience, still under construction, of the Territorial Development Policy in Bahia. It seeks to understand how participation takes place in the territorial management of the Territories of Identity as a public policy planning unit adopted by the state government since 2007, articulating the territorial approach to participatory democracy. We opted for qualitative research, seeking to maintain a balance arising from documentary, bibliographic and oral sources, however, with careful listening to the narratives presented by the interviewees, with regard to resumptions or new incursions into documents and theoretical-methodological analyses. The institutional context of the research was circumscribed to the scope of policies aimed at the areas of family agriculture and culture. The delimitation for choosing the research participants took place among the pioneers who acted or act within the scope of territorial policy, sometimes in public management, sometimes in civil society organizations, and who presented some degree of activism/militancy that linked them to their territories or to the territorial policy created in the state. The thesis presents its results from reflections on territory, democracy and participation based on the permanent movement of correlations of forces that institutes different political projects, in which the theoretical categories indicated, understood in their relational dimension, are present, at the time that they are appropriated by different social forces in a class society. The experience reinterpreted in the narrative of the social subjects presents new senses, meanings, and re-meanings of participation, according to the spaces where it takes place; the social, historical and geographic contexts; and the outlined territorialities. It was observed that there is a dispute over meanings in the propositions of territorial development projects, just as the notion of public management is also in dispute within democratic environments, whether in the spaces of the state apparatus or in the collegiate spaces of the public sphere. The narratives of the subjects that participated in the research also indicated a notion of sociopolitical participation beyond the sphere of claim and social control, reaching processes of agreement and negotiation on public policies in progress